Comparing the quantity and quality of randomised placebo- controlled trials of antibiotics for acute respiratory, urinary, and skin and soft tissue infections: a scoping review. Issue 4 (October 2020) - Bakhit, Mina; Hoffmann, Tammy; Santer, Miriam; Ridd, Matthew; Francis, Nick; Hummers, Eva; Clark, Justin; Hilliges, Carmen; Mar, Chris Del
No abstract available